2013
DOI: 10.1111/jocn.12202
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the relationships between residents and nursing homes nurses

Abstract: Dialogue and active listening with residents must be incorporated into the daily nursing care. It should be given the same attention to all residents, with special attention to residents with cognitive and functional difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Another helpful strategy might be to encourage staff to dine with residents and function as conversation facilitators during the meal. Past research has shown, however, that residents perceive staff do not value socialising (Palacios‐Ceña et al., ). Making expectations explicit and even developing policies around socialising with residents at mealtimes may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Another helpful strategy might be to encourage staff to dine with residents and function as conversation facilitators during the meal. Past research has shown, however, that residents perceive staff do not value socialising (Palacios‐Ceña et al., ). Making expectations explicit and even developing policies around socialising with residents at mealtimes may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these strategies have been reported in prior research; in particular, avoiding conflict (Palacios-Ceña et al, 2013), not complaining (Palacios-Ceña et al, 2013), and using passive approaches to getting needs met (Fiveash, 1998) have been noted as important ways to manage relationships with staff. Consistent with ‘having fun’ in this study, using humor, jokes, and teasing has been found to support peer relationship development even among persons with dementia (Hubbard et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies have focused on the relationships residents develop with staff (Cook and Brown Wilson, 2010, Heliker and Nguyen, 2010, McGilton and Boscart, 2007, McGilton et al, 2003, McGilton et al, 2012, Medvene et al, 2006, Nakrem et al, 2011, Palacios-Ceña et al, 2013) rather than other residents (see exceptions (Bergland and Kirkevold, 2008, Hubbard et al, 2003, Powers, 1991)), and very few have explored the process by which residents develop relationships with both staff and other residents in a single study (see exception (Brown Wilson et al, 2009)). As relationships with both peers and staff are important to residents, exploring relationship development with both in a single study is needed to more clearly understand any important differences or similarities.…”
Section: Introductionmentioning
confidence: 99%
“…However, spending time with new residents to establish positive relationships that would help new residents adjust to their new environment is an important aspect of nursing care (Palacios‐Cena et al . ). Through the development of supporting relationships, care staff can help allay residents' fears and worries and present positive aspects of the nursing home environment (Tse ).…”
Section: Discussionmentioning
confidence: 97%